The Public Forum - Myers, John (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
An in-Class Exercise : Congratulations! You have just been named director of the North Coast Community Mental Health Center. Before You Start Picking out your office furniture, the county commissioners would like you to participate in a community forum….